Nitrogen fertilization and association of elephant-grass (Pennisetum purpureum cv. Cameroon) with tropical forage legumes - Costa, Newton de Lucena (Pesquisa Agropecuaria Brasileira, 1995)
The agronomic performance of Pennisetum purpureum cv. Cameroon grown in pure stands fertilized with N (0, 50 and 100 kg of N/ha) and in mixture with six tropical forage legumes (Centrosema pubescens CIAT- 438, C. macrocarpum CIAT-5065, Pueraria phaseoloides CIAT-9900, Calopogonium mucunoides cv. Comum, Desmodium ovalifolium CIAT-350 and Stylosanthes capitata cv. Cook), were assessed in cutting experiment carried out at the Experimental Station of Presidente Médici in CPAF/Rondônia. The associations of the grass with C. macrocarpum CIAT-5065, C. mucunoides, D ovalifiolium CIAT-350, P. Phaseoloides CIAT-9900 and C. pubescens CIAT-438 provided forage yields equivalent of the dry matter yields obtained by grass alone plus 100 kg of N/ha. The grass in mixture with C. macrocarpum CIAT-5065, D. ovalifolium CIAT-350 and P. phaseoloides CIAT-9900 showed better agronomic performance, in relation to dry matter and crude protein yields, and satisfactory legume content and persistence in the associations. Apparent N fixation was higher for P. phaseoloides CIAT-9900 and D. ovalifolium CIAT-350, while the total amount of fixed N transfered to the grass were higher for D. ovalifolium CIAT-350, C. mucunoides and C. pubescens CIAT-438.